The voice of the silenced in Salman Rushdie’s Shame, Caryl Phillips’s Foreigners: Three English Lives, and Colum McCann’s - Talif, Rosli; Mani, Manimangai; Bahar, Ida Baizura; Wagaa, Intisar Mohammed (Australian International Academic Centre, 2017)
This article examines the implications of history in Salman Rushdie’s Shame (1983), Caryl Phillips’s Foreigners: Three English Lives (2007), and Colum McCann’s TransAtlantic (2013). History plays an important role in discriminating and distinguishing the proper characteristics of certain nations and people of a specific historical era. The purpose of the current paper is to scrutinize the historical components in the selected novels. These novels incarnate the authors’ visions of the silenced minorities depicted in the fictional plots. They embody the sense of individual sufferings at the time of human devastation and retardation caused by historical events. In essence, my study focuses on the authors’ abstract voices which are uttered through the fictional characters’ dialogic voices. That is, the authors portray the neglected and suppressed voices which need alleviation and freedom. Thus, the authors do not tend to express their authorial voices directly in the novels. Instead, they convey their literary meanings through the characters’ voices. Thus, my analysis will focus on both the authors’ implied voices and their manifestation in the characters’ direct fictional voices. The methodological analysis of the study will concentrate on the way by which the authors present the peculiarities of their fictional characters and discourses.